The synthesis, electric and magnetic properties of films witH eftectic composition of GаSb-MnSb system - S. F. Marenkin; O. A. Novodvorsky; V. V. Baranov; V. M. Trukhan; T. V. Shoukavaya; A. M. Struts (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the technology and electrical and magnetic properties study of eutectic GaSb-MnSb films are presented. Eutectic GaSb-MnSb films ranging in thickness from 80 to 130 nm have been grown on sapphire substrates by pulsed laser deposition using mechanical droplet separation.